Assessment of Trace Metal Content in Soils of Automobile Workshops around Bori Urban Area, Rivers State, Nigeria - Timothy, M. N.; Marcus, A. C.; Iyama, William Azuka (European Journal of Applied Sciences, 2022)
This study was designed to assess the concentration of trace metals (Cr, Cd, Mn, Ni, Pb, Zn) in soils of automobile workshops around Bori Urban, Rivers State, Nigeria. Samples were collected from three auto mechanic workshops within the Bori urban area, Rivers State, Nigeria. The soil samples were prepared by standard procedures, and analyzed using the Atomic Absorption Spectrophotometer, AAS (Solaar Thermo Elemental Atomic Absorption Spectrometer-Model SE 71906). Detectable concentrations (mg/kg) of the metals, Zn, Mn, Pb, Cd, Ni and Cr were 4.05 ± 1.02, 9.64 ± 0.71, 13.39 ± 2.28, 2.46 ± 0.42, 2.86 ± 0.79 and 2.76 ± 0.99 respectively. The concentrations and contamination factors (CFs) across the three auto mechanic garages were of the order, Pb > Mn > Zn > Cd > Ni > Cr and Cd > Cr > Ni > Mn > Pb > Zn respectively while the pollution load index (PLI) values for the three auto mechanic garages were all greater than 1, indicating a decline in the soil quality for the three studied sites following the order station 3 > station 1 > station 2. The Geo accumulation index (Igeo) revealed that the soils were extremely contaminated by Cd and were all contaminated with trace metals when compared with regulatory standards such as WHO and world average values in shale. Therefore, regular monitoring of the soil in the studied sites be carried out to mitigate dangers implicit in the continued presence of the metals determined.